Characterization of Sulfur-Compounds as Chemotaxonomic Markers in the Essential Oils of Allium Species by Solvent-Free Microwave Extraction and Gas Chromatography–Mass Spectrometry. (4th March 2019) - Ikram, Rabia; Low, Kah Hin; Hashim, Najihah Binti; Ahmad, Waqas; Nasharuddin, Muhammad Nazil Afiq
Abstract: Allium species were examined to authenticate the chemotaxonomic controversy about these plants by analyzing their extracted compound profiles. Essential oils of various species were isolated using conventional hydro-distillation and solvent-free microwave extraction (SFME). A comparison of the isolation procedures was performed. The presence of sulfur compounds in the Allium genus is a prominent characteristic for their medicinal uses. These components were characterized using two-way hierarchical cluster analysis (HCA) and principal component analysis (PCA). The variation of sulfur-compounds was performed by qualitative analysis of Allium species by gas chromatography–mass spectrometry (GC–MS). 2, 4-Dimethyl-5, 6-dithia-2, 7-nonadienal, 4, 6-diethyl-1, 2, 3, 5-tetrathiolane, and 5, 7-diethyl-1, 2, 3, 4, 6-pentathiepane were revealed as potential chemotaxonomic markers for all of the Alliums examined in this study. These markers may be used to provide improved systematics for other Allium species.